Effective Multidisciplinary Search Strategies for Assistance Animals: A Librarian's Perspective - Fausak, Erik Davis (Frontiers in Veterinary Science, 2019)
Successful search strategies are based on good background knowledge and a focused clinical research question. Due to the multidisciplinary nature of research involving assistance animals means there is no one universal database to answer all research questions. The topic of assistance animals can yield better results when creating subheadings based on discipline focus. Subheadings have been divided into ethicolegal, sociocultural, psychobehavioral, and medical/veterinary. Each subheading, or discipline, has their own specific databases that will yield higher relevant content than others. Contacting local academic librarians and utilizing search guides created by those librarians can lead to successful search strategies. The goal of this article is to create a template for successful search strategies in assistance animals. 89 subject guides curated by academic librarians are reviewed to identify strong databases for each topic of ethicolegal, sociocultural, pscyhobehavioral, and medical/veterinary topics in relationship to assistance animals. A live subject guide has been created and maintained at https://www.library.ucdavis.edu/guide/assistance-animals/